Activation of Methanogenesis by Cadmium in the Marine Archaeon Methanosarcina acetivorans - Lira-Silva, Elizabeth; Santiago-Martínez, M. Geovanni; Hernández-Juárez, Viridiana; García-Contreras, Rodolfo; Moreno-Sánchez, Rafael; Jasso-Chávez, Ricardo (PLOS ONE, 2012)
Methanosarcina acetivorans was cultured in the presence of CdCl2 to determine the metal effect on cell growth and biogas production. With methanol as substrate, cell growth and methane synthesis were not altered by cadmium, whereas with acetate, cadmium slightly increased both, growth and methane rate synthesis. In cultures metabolically active, incubations for short-term (minutes) with 10 µM total cadmium increased the methanogenesis rate by 6 and 9 folds in methanol- and acetate-grown cells, respectively. Cobalt and zinc but not copper or iron also activated the methane production rate. Methanogenic carbonic anhydrase and acetate kinase were directly activated by cadmium. Indeed, cells cultured in 100 µM total cadmium removed 41–69% of the heavy metal from the culture and accumulated 231–539 nmol Cd/mg cell protein. This is the first report showing that (i) Cd2+ has an activating effect on methanogenesis, a biotechnological relevant process in the bio-fuels field; and (ii) a methanogenic archaea is able to remove a heavy metal from aquatic environments.